DEFISIT OLFAKTORI DAN PENINGKATAN RISIKO GANGGUAN FUNGSI BAHASA PADA LANSIA - Stevanie Regina, Josephine Retno Widayanti, Nelly Tina Widjaja, Yuda Turana (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION NAMING IMPAIRMENT AND OLFACTORY DEFICIT CAN BE FOUND EARLY IN THE COURSE OF THE NEURODEGENERATIVE DISEASE WHICH ASSESSMENT OF THESE FUNCTIONS CAN BE USEFUL FOR EARLY DIAGNOSIS OF NEURODEGENERATIVE DISEASE